Progress in Cultural Heritage Preservation 4th International Conference, EuroMed 2012, Lemessos, Cyprus, October 29 -- November 3, 2012, Proceedings - Ioannides, Marinos; Fritsch, Dieter; Leissner, Johanna; Davies, Rob; Remondino, Fabio; Caffo, Rossa (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the refereed proceedings of the 4th International Conference on Progress in Cultural Heritage Preservation, EuroMed 2012, held in Lemesos, Cyprus, in October/November 2012. The 95 revised full papers were carefully reviewed and selected from 392 submissions. The papers are organized in topical sections on digital data acquisition technologies and data processing in cultural heritage, 2D and 3D data capture methodologies and data processing in cultural heritage, 2D and 3D GIS in cultural heritage, virtual reality in archaeology and historical research, standards, metadata, ontologies and semantic processing in cultural heritage, data management, archiving and presentation of cultural heritage content, ICT assistance in monitoring and restoration, innovative topics related to the current and future implementation, use, development and exploitation of the EU CH identity card, innovative technologies to asses, monitor and adapt to climate change, digital data acquisition technologies and data processing in cultural heritage, 2D and 3D data capture methodologies and data processing in cultural heritage, on-site and remotely sensed data collection, reproduction techniques and rapid prototyping in cultural heritage, 2D and 3D GIS in cultural heritage, innovative graphics applications and techniques, libraries and archives in cultural heritage, tools for education, documentation and training in CH, standards, metadata, ontologies and semantic processing in cultural heritage, damage assessment, diagnoses and monitoring for the preventive conservation and maintenance of CH, information management systems in CH, European research networks in the field of CH, non-destructive diagnosis technologies for the safe conversation and traceability of cultural assets.